Rancang Bangun Sistem E-Absensi Web Menggunakan Laravel (Studi Kasus: RSUD Labuha) - Lua, Muhammad Febriyan; Sulistyo, Wicaksono Yuli (Insect (Informatics and Security): Jurnal Teknik Informatika, 2025)
A common problem in attendance management is the manual system employed at RSUD Labuha, which is prone to inefficiencies, human errors, and difficulties in real-time monitoring. This study aims to address these issues by designing and developing a web-based e-attendance system using the Laravel framework to improve the efficiency and accuracy of employee attendance management. The system is intended to provide an automated solution for digital attendance recording, real-time monitoring, and integrated reporting. The research adopts the Waterfall methodology, which provides a structured and sequential approach to system development. Data collection was conducted through direct observation at RSUD Labuha to identify workflow patterns and system requirements. The system is developed using PHP programming language integrated with the Laravel framework. All functionalities are tested in a localhost environment using Black Box Testing to ensure validity and reliability. The result of this study is a fully functional e-attendance system successfully implemented and tested in the localhost environment. All core features, including digital attendance recording, reporting, and dashboard management, are proven to be operational and effective. The primary limitation of this study is the inability to conduct full-scale implementation and testing in a live hosting environment due to technical and administrative constraints. Nevertheless, this web-based e-attendance system successfully fulfills the research objectives by delivering a deployable digital solution tailored for attendance management at RSUD Labuha. This study contributes a customized system design for the institution, with its architecture and findings serving as a reference for similar future projects.